A programme design, theory and implementation evaluation of the Khanyisa Programme - Guattari-Stafford, Thomas (Organisational Psychology, 2020)
This study is a formative evaluation of a youth development programme which places volunteers as 'reading buddies’ in grade 2 classes in schools in the Western Cape. The study assesses the implementation of the school placement component of the programme - comparing the actual and intended implementation, as well as describing the volunteers’ experience thereof. The evaluation uses a mixed methods approach, combining surveys with volunteers and teachers with an electronic volunteer diary and volunteer focus group. Additionally, the evaluation establishes a common understanding of the programme logic (through a comparison of four stakeholder perspectives) and assesses the plausibility of the programme achieving its intended impact considering the available literature. The study includes surveys programme volunteers (n = 23) and school teachers (n = 30), interviews with programme staff (n = 4) and focus groups with programme staff and volunteers (n = 16). Ethical clearance for the study was obtained through the University of Cape Town’s Commerce Faculty Ethics in Research Committee. The evaluation findings indicate that the school component is being implemented as intended. However, volunteers raised concerns of unproductive time spent at schools, a perceived lack of respect from learners and tensions with school staff - especially after incidents where corporal punishment was reported. These findings suggest the need for an improved monitoring system to facilitate real-time responses to challenges experienced by the volunteers, as well as a form of mediation between volunteers and school staff when tensions occur. Regarding the plausibility of the programme logic, the evaluation finds a lack of evidence to suggest the programme’s intended impact is likely to be achieved. As such, revisions to the programme design are suggested.